Examining the Variables Impacting the Efficiency of Methods and Resources Utilized by Banks in Identifying Training Requirements - Dr. Jaspreet Kaur (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Training involves enhancing employees' knowledge and skills for specific tasks, thereby boosting organizational effectiveness. In today's fiercely competitive global business landscape, training and development are pivotal for effective human resource management. Organizations must design training policies and programs and continually train their workforce. An effective training system comprises processes that convert organizational inputs into outputs aligned with organizational requirements. This paper aims to analyse trainees' perspectives on the effectiveness of methods and resources used in Commercial Banks for identifying training needs.